Sebastiano Ricci impresario in angustie a Venezia: i guai della stagione 1718-1719 al Sant’Angelo - Gianluca Stefani (Drammaturgia, 2016)
Sebastiano Ricci was not only one of the greatest painters of the 18th century, but an active impresario in the Venetian opera houses at the beginning of the early 18th century. Thanks to the rediscovery of some notarial and judicial documents in the Archivio di Stato of Venice, we can reconstruct the circumstances under which he became manager of the Teatro di Sant’Angelo in the season 1718-1719, a season marked by his succession to the previous impresario Antonio Moretti (known as Modotto) and by his legal dispute with the violinists Giovan Battista and Ludovico Madonis at the tribunal ‘del Forestier’.